Combining resources and conversion factors - Azmoodeh, Mohammad; Haghighi, Farshidreza; Motieyan, Hamid (TeMA - Journal of Land Use, Mobility and Environment, 2022)
A growing body of recent studies involves the social effects of distributive justice in the field of transportation, which mostly can be traced back to the studies of spatial mismatches, income, or gender inequality. So, this paper seeks to address challenges related to the conceptualization of capability and proposes a new aggregated framework to draw the connection between Resources, Conversion Factors, and Capabilities as the key terms of the Capability Approach. Consequently, by classifying the resources and conversion factors to "individual characteristics," "transportation options," and "urban living environment" dimensions, the model would provide an index that expresses the level of capabilities called the Capability Index (CI). The results of scenarios evaluated in this paper demonstrate that the significant difference in the capabilities is mainly affected by car ownership and income variables with 2.214 and 0.223 Cohen’s d effect size, respectively. Also, disability in the young age group causes a more significant reduction in their capability index than their old counterparts. The model demonstrates the need to highlight the capability notion and the need for improving new methods to underscore human characteristics as the focal point in urban policy-making.